Identification of a gene required for membrane protein retention in the early secretory pathway - Nishikawa, S; Nakano, A (Proceedings of the National Academy of Sciences - PNAS, 1993)
The yeast SEC12 gene product (Sec12p) is an integral membrane protein required for the protein transport from the endoplasmic reticulum (ER) to the Golgi apparatus. Although this protein is almost exclusively localized in the ER, a significant fraction of Sec12p is modified by an enzyme that resides in the early compartment of the Golgi apparatus, suggesting that Sec12p is cycling between the ER and the early Golgi. We have taken a genetic approach to investigate the retention mechanism of Sec12p. Analysis of mutants that are defective in the retention of the Sec12-Mf alpha 1 fusion protein in the early secretory compartments has identified a gene, RER1. A recessive mutation in RER1 causes mislocalization of the authentic Sec12p as well as two different Sec12 fusion proteins to the late Golgi apparatus and even to the cell surface. However, the rer1 mutant is not defective in the retention of an Er-resident soluble protein, BiP, suggesting that soluble and membrane proteins are retained in the ER by distinct mechanisms